Transport mechanism of eurycomanone from Eurycoma longifolia Jack across Caco-2 cells model - Wu-Yan Guo; Huan Zhang; Yue-Yang Zhang; Shu-Yan Wang; Jian Ren; Yong-Qing Jia; Rui Liu; Bo Zhang (Journal of Food Bioactives, 2022)
Eurycomanone is the main active ingredient of Eurycoma longifolia Jack with anti-cancer, anti-malaria, improving male sexual dysfunction and other effects.The poor lipid solubility of eurycomanone is potential reason for its low bioavailability. However, the transmembrane absorption mechanism has not been reported. In this study, the Caco-2 cell monolayer model was used to investigate the influence of different factors on the eurycomanone transmembrane absorption, including time, concentration, temperature, P-glycoprotein inhibitors (verapamil or cyclosporin A) and collateral transport enhancer (sodium desoxycholate or EDTA).The results showed that the apparent permeability coefficient (Papp) of eurycomanone was lower than 10-6 cm/s with poor oral absorption. The Papp was not dependent on concentrations or temperatures. The addition of paracellular transport enhancer promoted the absorption of eurycomanone(P < 0.05), whereas p-glycoprotein inhibitors had no effect.Taken together, this study indicated that absorption of eurycomanone  may undergo passive transmembrane transport and paracellular transport.